Inflammatory response of miniature horses subjected to open and half‐closed orchiectomy techniques. (18th April 2021) - de Moura Alonso, Juliana; de Melo‐Neto, Gabriel Barbosa; dos Santos, Bruna; Mogollón García, Henry David; Paim, Kamila Pinheiro; Pinheiro Ferreira, João Carlos; Santos Schmidt, Elizabeth Moreira; da Silva, Amanda Nogueira Ferreira; da Cunha, Grazielly Marques; Takahira, Regina Kiomi; Ferreira Canuto, Lucas Emanuel; Papa, Frederico Ozanam; et al.
Abstract: Background : This study aimed to evaluate the inflammatory response of miniature horses subjected to open and half‐closed orchiectomy by physical examination, blood cell count, peritoneal fluid evaluation, total plasma protein, fibrinogen, and serum amyloid A (SAA) concentrations. Methods : Thirteen male healthy miniature horses were divided into two groups, according to the surgical approach: half‐closed technique (HCT) and open technique (OT). The HCT group was subjected to ligation of the spermatic cord followed by its sharp incision, and closure of the vaginal tunic, and the OT group was only submitted to cord ligation. Prior to, and at 1, 2, 3 and 5 days after the surgery, a general and specific physical examination, blood cell counts, total plasma protein, peritoneal fluid evaluation, fibrinogen, and SAA concentrations were performed. Results : Higher postoperative perilesional oedema, rectal temperature, and fibrinogen were observed in the HCT group. Groups did not differ as to SAA concentrations. The evaluated local and systemic inflammatory profile demonstrated that, as expected, surgery resulted in inflammation in both groups. Conclusions : The group subjected to the HCT showed a more intense and lasting inflammatory response. However, despite the different postoperative inflammatory profiles, both groups presented a favourable outcome and recovery.